Oxford handbook of anaesthesia - Allman, Keith G.; Wilson, Iain H. (Oxford handbooks, 2011)
The bestselling Oxford Handbook of Anaesthesia has been completely updated for this new third edition. All chapters have been rewritten and a number of new authors have been brought on board to add their expertise and knowledge. Additional new material includes regional anaesthesia, and a comprehensive section on anaesthesia for interventional radiology, a rapidly expanding field of medical practice with particular implications for anaesthesia.